Evaluation of Health Education Services at Primary Health Care Centers in Kirkuk Governorate - hama, Burhan; Khalifa, mohammed (Iraqi National Journal of Nursing Specialties, 2012)
Objectives: To evaluate health education services at primary health care centers in Kirkuk Governorate. Methodology: A descriptive (evaluative) study a simple random sample of (384) person is selected through the use of probability sampling approach. The sample of study is divided into three groups which include (320) consumers, (32) health educators and (32) organization structure (in the (32) primary health care centers). They are comprised of three questionnaires and overall items included in these questionnaires are (157) items. The study included assessment of organization structure, such as work place, material, resources, and workforce, demographic characteristics of care providers and consumers and activities and duties of providers. Interviews are conducted with directors of primary health-care centers, consumers and health educators. Results: The findings of the study indicate that there is over- load of target population on primary health care centers, poor designed building, program statistical and data reporting system was poor, decrease core financial support and inadequacy of funding for primary health care centers, there is increased demand and decreased supply of primary health care health educators and Poor of strategies of training and development for health educators and poor health education lectures for consumers in primary health-care center . Recommendations: The study establishment of buildings for primary health care centers according to the numbers of consumers within the geographical area. A Primary care system must grow and be nourished. Health educators need to be expanded to meet growing community needs, once in place, must be supported so it can continue and thrive for program reporting use to project the supply of health educators and support of strategies of health education for consumers.